Non-depleting energy in the museum - Bapoğlu Dümenci, Sırma Seda; Aral, Neriman; Gürsoy, Figen; Demir, Emin; Kadan, Gül; Tosun, Selim; Öz, Nur Sena; Hafızoğlu, Gökçe; Tosun, Cansel; Çelik, Şule; Geçen, Mehmet; Yelek, Özge; et al. (Frontiers in Psychology, 2023)
The present study aimed to uncover whether the renewable energy education carried out in a museum has an impact on awareness of renewable energy and the environment among children and their parents. The study was carried out with two groups of 65 children aged six years and their parents (n = 47). The findings revealed significant differences between the pretest and posttest in favor of the pretest and between pretest and follow-up test in favor of follow-up test, but there was no significant difference between posttest and follow-up test. We determined It was observed that the children had a considerable willingness to participate in the sessions and used the names of renewable energy sources in their follow-up drawings or their remarks on the drawings. Moreover, given the parents' statements, we discovered that the children acquired considerable awareness of the environment and efficient energy consumption and became acting more consciously toward renewable energy sources.